2022
DOI: 10.3389/fmicb.2022.814864
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Community Structure and Diversity of Seed-Vectored Endophytic Fungi in Alpinia zerumbet

Abstract: Endophytic fungi act as seed endosymbiont, thereby playing a very crucial role in the growth and development of seeds. Seed-vectored endophytic fungi establish an everlasting association with seeds and travel from generation to generation. To explore the composition and diversity of endophytic fungi in Alpinia zerumbet seeds, high-throughput Illumina MiSeq sequencing was employed for the following stages: fruit formation period (YSJ1), young fruit period (YSJ2), early mature period (YSJ3), middle mature period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…The FUNGuild database is of great help in studying the relationships between fungi and ecology, but it has its own limitations that cannot be ignored. Yan et al found that Aspergillus candius was classified as a saprotroph in the FUNGuild database, while their report had classified it as an endophytic fungus in plants [ 74 , 75 ]. The data of the FUNGuild database are not updated in real time, and a large amount of fungal information has not been collected.…”
Section: Discussionmentioning
confidence: 99%
“…The FUNGuild database is of great help in studying the relationships between fungi and ecology, but it has its own limitations that cannot be ignored. Yan et al found that Aspergillus candius was classified as a saprotroph in the FUNGuild database, while their report had classified it as an endophytic fungus in plants [ 74 , 75 ]. The data of the FUNGuild database are not updated in real time, and a large amount of fungal information has not been collected.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the widespread fungal genus Alternaria are commonly found in a broad diversity of niches and environmental substrates ( Lawrence et al, 2013 ; Woudenberg et al, 2013 ). Several recent surveys of various plant microbiomes have demonstrated that Alternaria is often one on the most abundant fungal genera recovered (e.g., Johnston-Monje et al, 2021 ; Latz et al, 2021 ; Morales Moreira et al, 2021 ; Hafez et al, 2022 ; Yan et al, 2022 ). While some species may be saprobes or harmless endophytes, many other species are economically significant pathogens of important agricultural crops ( Thomma, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are a variety of microorganisms in the ecosystem that can mutualism with plants and play a role in the resistance of plants to biotic and abiotic stresses ( Xiao et al, 2022 ; Yan et al, 2022 ). Arbuscular mycorrhizal fungi (AMF) are ubiquitous in soil environments and interact with most plants through mycorrhizal structures ( Xiao et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%